A modified surgical technique: lateral crossed-tensioned K-wires combined with external fixation for supracondylar humeral fractures in school-aged children - Zhu, Huanye; Wang, Mengyao; Gao, Chao; Zheng, Huajiang; Cao, Jin (Frontiers in Pediatrics, 2025)
ObjectiveThis study evaluated the clinical efficacy of a modified surgical technique—lateral crossed-tensioned Kirschner wires (K-wires) combined with external fixation—for treating supracondylar humeral fractures in school-aged children.MethodsBetween April 2022 and April 2023, 45 school-aged children (ages 6–13) with supracondylar humeral fractures were retrospectively included in this study. The modified surgical technique involving lateral crossed-tensioned K-wires combined with external fixation was employed to facilitate early functional recovery without the need for plaster immobilization. The postoperative follow-up included a radiographic evaluation, assessment of elbow joint functional recovery, and patient satisfaction surveys.ResultsAll the patients were followed up for 6–18 months. Five patients developed pin site infections, which were successfully managed with routine care. No cases of non-union, K-wire migration, or dislocation were observed. Based on their Flynn scores, 93.3% of the patients achieved excellent elbow joint function at 1 month postoperatively, increasing to 97.8% at 3 months and remaining stable at 6 months. No instances of elbow varus deformity were observed during follow-up. The patients and their families reported high satisfaction levels and recommended this technique for similar fractures in other children.ConclusionsThe use of lateral crossed-tensioned K-wires combined with external fixation for supracondylar humeral fractures in children yields satisfactory results, promotes early functional recovery of the elbow joint, facilitates a quicker return to school activities, and improves patient satisfaction. This technique is a viable alternative for managing supracondylar humeral fractures in school-aged children.